Accumulation of phosphorus fractions in typic Hapludalf soil after long-term application of pig slurry and deep pig litter in a no-tillage system - Guardini R. (2012)
In this paper we explore the accumulation of different phosphorus (P) fractions in soil submitted to successive applications of pig slurry (PS) and deep pig litter (DL). After 88 months of no-till crop cycles, soil samples were collected in the following treatments: control (C), PS applications equivalent to 90 and 180 kg N ha-1 (PS90 and PS180), and DL applications equivalent to 90 and 180 kg N ha-1 (DL90 and DL180). The cumulative application of P of the C, PS90, PS180, DL90 and DL180 treatment was 0, 303, 606, 825 and 1650 kg P ha-1, respectively. The soil samples were then submitted to P chemical fractionation. Successive applications of 303 and 606 kg P ha-1 in PS form and 825 and 1.650 kg P ha-1 in DL form increased P levels down to 20 cm depth, especially in the labile inorganic fraction extracted by anion exchange resin and 0.5 M NaHCO3 and to a lesser extent extracted by 0.1 M NaOH. Successive additions of PS180 and DL180 increased the levels of organic P extracted by 0.5 M NaHCO3, 0.1 M NaOH and 0.5 M NaOH, and successive applications of PS and DL caused P accumulation in the soil profile, especially in labile fractions. This increased the availability to plants, but also increases the potential for environmental contamination. © 2012 Springer Science+Business Media B.V.